(untitled) (European Journal of Marketing and Economics, 2025)
The purpose of this research aims to study and collect data with detailed information of the cross Thai-Cambodian border’s commerce in the past from French’s documents and to provide information as a guideline for potential development of Thai-Cambodian Border Trade. The method used in this research is the qualitative research. The research instrument used historical methods by collecting information from primary and secondary sources, then to analysis process. The research discovered the pattern of trade between Cambodia and Siam that started to be affected when borders were established. Since Cambodia was under French’s rule as one of French’s nation, France tried to delimit and demarcate the boundary lines which divided the community that once cohabitated into a community under new nation state. In each area, traditions, rules and laws are different, but people lived along the border continued to bring their goods to exchange for their livings. This habit is still continuing, even the living communities are divided into different countries. For such reason, it was the source of "Border trade” in western concept. The Thai-Cambodian border’s trade during that period under the French protectorate of Cambodia was effected because of the rules and law which illustrated the sovereignty of the land. At the same time, customs have been defined including several details that have affected the traditional trade. The border’s commerce was more sophisticated. The products had transformed according to the needs of the developed world market and social conditions.